BEYESIAN ESTIMATION FOR INTERFERENCE TEST - ARISETYAWAN (NIM. 20107006), ANDIKA
Inteference test is one of reservoir test which use to know connection between wells, so that interwell properties like transmissivity and storativity can be estimated, including initial reservoir system. The advantage of interference test compared with any other methods is giving significant estimation of permeability during the test. It uses derivative method and Ensemble Kalman Filter (EnKF) to estimate parameter transmissivity and storativity at Kawerau geothermal field, New Zealand. The results show that derivative method give better estimation than EnKF.